Coalition formation and the ancillary benefits of climate policy - Michael Finus; Dirk T. G. Rübbelke (Fondazione Eni Enrico Mattei (FEEM), 2008)
Several studies found ancillary benefits of environmental policy to be of considerable size. These additional private benefits imply not only higher cooperative but also noncooperative abatement targets. However, beyond these largely undisputed important quantitative effects, there are qualitative and strategic implications associated with ancillary benefits: climate policy is no longer a pure but an impure public good. In this paper, we investigate these implications in a setting of non-cooperative coalition formation. In particular, we address the following questions. 1) Do ancillary benefits increase participation in international environmental agreements? 2) Do ancillary benefits raise the success of these treaties in welfare terms?
Keywords: C72; H87; Q54; 330; Ancillary Benefits; Climate Policy; Coalition Formation; Game Theory; Impure Public Goods